DNA profile of commercial pineapples in Malaysia by using SSR markers - Siti Norhayati Ismail; Nurul Shamimi Abdul Ghani; Shahril Ab. Razak; Rabiatul Adawiah Zainal Abidin; Mohd Nizam Zubir; Rozlaily Zainol (Penerbit Universiti Kebangsaan Malaysia, 2021)
Nine commercial varieties of pineapples in Malaysia (Josapine, Maspine, MD2, Sarawak, Gandul, N36, Moris, Crystal Honey and Yankee) were collected from various places in Peninsular Malaysia and analysed for cultivar identifications using nine simple sequence repeat (SSR) markers. A total of 27 alleles have been observed which ranged from 2 to 5 with an average of 3 alleles per locus. The polymorphic information content (PIC) value ranged from 0.3426 (Acom_82.8) to 0.6561 (Acom_67.2) with a mean of 0.4524 while the heterozygosity value ranged from 0.1097 (TsuAC021) to 0.8010 (TsuAC039) with a mean of 0.5481. The pairwise Nei’s genetic distances had also been calculated and the value ranged from 0.0562 (Gandul and Josapine) to 0.6383 (MD2 and Yankee) with an average value of 0.3169. The above data emphasised a moderate level of polymorphisms among the nine varieties. A dendrogram was constructed by using the unweighted pair group method with arithmetic mean (UPGMA) which showed all the nine successfully differentiated pineapple commercial varieties. A principal coordinate analysis (PCoA) was also had been generated which revealed an agreement with the dendrogram output. Therefore, these nine SSR markers can be used to identify the nine selected commercial varieties to ensure pure planting materials.